Inaccuracy of An Examination of Grammatical Error - Majid, Shabri Abd. (Majapahit Journal of English Studies, 2024)
When it comes to the construction of a communication process, grammar plays a significant part. It is utilized to make a clear declaration about the time at which a verb happens. The purpose of this study is to identify grammatical faults in the translation of abstracts from the Indonesian language to English that were produced by Google Translate. These errors pertain to tense, active, and passive voice abstracts. In this particular research project, the research method that was utilized was the descriptive qualitative method. The twenty abstracts that were retrieved from the repository at the University served as the population for this investigation. Documentation and checklists were the instruments that were utilized in the process of doing the data collection. When analyzing the data, Keshavarz's (1999) hypothesis was utilized. Following an examination of the data, it was discovered that the most common error that Google Translate generated was related to the use of tense. In the meanwhile, errors involving active and passive voices were only sometimes discovered. It is possible to conclude that Google Translate, operating as a tool, is unable to determine the tense of the sentences that are being translated. This is a possibility since tenses are strongly connected to the context in which the moment a verb occurs in a sentence, which is something that can only be broken down and comprehended by humans.